Understanding the impact of environmental variability and fisheries on the red sea urchin population in Baja California - Medellín–Ortiz, Alfonso; Montaño–Moctezuma, Gabriela; Álvarez–Flores, Carlos; Santamaría-del-Ángel, Eduardo; García–Nava, Hector; Beas–Luna, Rodrigo; Cavanaugh, Kyle (Frontiers in Marine Science, 2022)
Introduction The red sea urchin fishery is one of the most important fisheries in Baja California and the only urchin fishery in México; yet little is known on understanding how local, regional, and oceanic environmental variability may affect red sea urchin populations. Methods We analyzed how food availability, predator abundance and environmental variability could affect red sea urchin populations developing generalized linear models under different temperature conditions: Pre-heat wave, heat wave, and post–heatwave, including sites where sea surface temperature was above, below, and on average. Models included: a) biological variables: Macrocystis pyrifera (kelp) biomass, red sea urchin (Mesocentrotus franciscanus) density, sheephead (Semicossyphus pulcher), kelp bass (Paralabrax clathratus) and spiny lobster (Panulirus interruptus) catches, and b) oceanographic variables: sea surface temperature, wave power, upwelling index, multivariate El Niño index and North Pacific Gyre Oscillation index. Results Between 65 and 82% of the variability observed in red sea urchin populations was explained by different combinations of variables, depending on the thermal condition analyzed. We observed that local environmental variability, such as food availability and predator harvest are highly important factors in determining red sea urchin population changes, compared to regional and oceanic scale variables such as upwelling, El Niño, or the North Pacific Gyre Oscillation. Results show that the relative importance of these variables changed depending on the spatial and temporal scale being analyzed, meaning that under “normal or average” conditions one set of variables is important, compared to extreme environmental conditions such as El Niño or “the Blob” when a different set of variables explained the observed variability. Urchin predators’ catches were correlated with urchin density during the pre-heatwave scenario, suggesting that under “average temperature” conditions the effect of fishing on predators, and consequently on urchin density is higher than local temperature, the most important variable during warm conditions. Discussion This study suggests that in Baja California, red sea urchin harvest has become the most important red sea urchin population control, so efforts should be encouraged and supported by state and federal agencies to promote more resilient ecosystems in the face of environmental uncertainty. Improving management of the commercial species that inhabit kelp forest, could yield benefits for the entire ecosystem, fishers, and the red sea urchin population in Mexico.